THE INFLUENCE OF HOLISTIC MARKETING AND PRODUCT QUALITY ON PURCHASING DECISIONS AT DEVIL'S MACARONI - Makthum, Rohiqil; Suharto, Akmad; Rusdiyanto, Rusdiyanto (Univesitas Muhammadiyah Tangerang, 2025)
Increasingly competitive and dynamic markets are placing manufacturers and marketers under greater pressure to understand the factors that influence consumer purchasing decisions. In this context, holistic marketing and product quality have emerged as two important variables in influencing consumer behavior. This research aims to determine and analyze the influence of internal marketing, integrated marketing, relationship marketing and product quality on purchasing decisions for the Adeeva Group, Jember Regency. This type of research uses quantitative methods with a sample size of 110 respondents and uses non-probability sampling techniques with purposive sampling techniques, using data collection techniques in the form of questionnaires to respondents. The data analysis technique for this research uses instrument testing, classical assumptions and multiple linear regression, hypothesis testing and the coefficient of determination R2. The analysis results obtained show that food quality, price, live streaming and Instagram social media have a positive and significant influence, both partially and simultaneously, on product purchasing decisions at the Adeeva Group, Jember Regency 0.953 or 95%